(untitled) (INTERNATIONAL SEMINAR, 2024)
Optimizing a learning model that focuses on teachers is an effort to improve the quality of the teaching and learning process by emphasizing the main role of teachers in transferring knowledge to students. One method commonly used in this approach is a lecture, where the material is presented orally by the educator. This research aims to identify factors that influence the effectiveness of the lecture method in teacher-oriented learning, as well as propose strategies to optimize this method. This case study was conducted at the university education level, where the analysis focuses on the interaction between educators and students during the lecture process, as well as its impact on students’ understanding of the material received. The research results show that factors such as teaching style, use of visual aids, and variations in material delivery play an important role in increasing students’ attention and understanding. Therefore, to optimize the lecture method in a teacher-focused learning model, it is necessary to increase teacher skills in managing the class and utilizing various learning media. This aims to create a more dynamic and interesting atmosphere for students. This research also recommends training for teachers to master more effective lecturing techniques and emphasizes the importance of continuous evaluation of the teaching strategies implemented.